Whey proteins-epicatechin interactions in a model specialized food product treated by high pressure. Issue 2 (3rd April 2019) - Clion, Valentin; Pottier, Laurence; de Lamballerie, Marie
ABSTRACT: The addition of protein to fruit, as a protein-enriched food, can modify the nutritional intake of both components. To mimic the protein-polyphenol interaction, a model product composed of whey protein (WP) and epicatechin (epi) was evaluated with various compositions (0%–20% polyphenol/protein). The effect of high pressure (HP) processing as a preservation method was tested and compared with control samples. The formation of complexes was evaluated by nephelometry, and oxygen radical absorbance capacity (ORAC) measurement was used to examine the variation in antioxidant capacity. Interactions were observed at the proportion of epi/WP 1%–2% and 15%–20% mass ratio. A high increase in turbidity, due to WP denaturation, was observed after HP processing. ORAC assays show that the antioxidant capacity of the epicatechin solution was improved by 22% with WP addition at epi/WP 1%. Preservation by high pressure slightly reduced antioxidant capacity.